Tindakan Berteologi Anak Negeri Tuhaha Dalam Tradisi Mangkok Enam Bulan - Agustinus O. Lopuhaa (P3M POLITEKNIK NEGERI AMBON, 2025)
Mangkok Enam Bulan ritual is one of the rites that is still maintained by the Tuhaha society in the context of their lives. This rite becomes one of their identities, which is based on the cognitive creations of their ancestors as a result of migration from Kohu to Aimahono.Mangkok Enam Bulan ritual is carried out in three stages, namely the preparation stage, the morning stage and the evening stage. This entire series of rites reflects the traditional identity and Christian identity which is very strong in Tuhaha.Mangkok Enam Bulan ritual is reflects an act of theology of the Tuhaha society in their relationship with God and the universe. Their theological actions reveal their awareness of God's presence and guidance in their history, and also how they view the sacredness of space and time.The research was conducted using a qualitative methodology that focused on observation using in-depth interview techniques. Meanwhile, data analysis uses a hermeneutic mode regarding the strong traditional struggle between the gospel and the cultural forces of society. This struggle is an act of theology of the society, as a reflection of God's inclusion in their history.Keywords: Mangkok Enam Bulan, Theological Action